Pengaruh Keunikan Produk dan Kualitas Produk terhadap Minat Beli Ulang Konsumen pada Produk Rengginang Comel di Ekang Anculai Bintan, Kepulauan Riau - Syimli Amanda Hasibuan; Aulia Rahman; Siti Maheran (EMASHA: Jurnal Ekonomi, Manajemen dan Akuntansi Syariah, 2025)
This research aims to analyze the influence of product uniqueness and product quality on consumer repurchase intention for Rengginang Comel products in Ekang Anculai, Bintan. The type of research used is quantitative with a survey approach. The research population includes all Rengginang Comel customers during the 1 September 2024 – 20 February 2025 period. The sample size used in this study is 72 respondents, determined using the Slovin formula. Data was collected through questionnaires and analyzed using multiple linear regression analysis. The results of the partial t-test show that product uniqueness (X1) has a positive and significant effect on repurchase intention (Y), with a t-value of 3.242 and a significance of 0.002 (< 0.05). Similarly, product quality (X2) also has a positive and significant effect on repurchase intention (Y), with a t-value of 4.781 and a significance of 0.000 (< 0.05). Furthermore, the results of the simultaneous F-test indicate that product uniqueness and product quality together have a positive and significant effect on repurchase intention. This is evidenced by an F-value of 34.446, which is greater than the F-table (3.130), and a significance of 0.000 (< 0.05). The coefficient of determination (Adjusted R Square) of 0.485 indicates that 48.5% of the variation in repurchase intention can be explained by product uniqueness and product quality, while the remainder is influenced by other factors.